2018
DOI: 10.1002/jcp.26809
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolated morphology of chordoma cells is dependent on cytokeratin intermediate filaments

Abstract: Notochordal cells (NCs), characterized by their vacuolated morphology and coexpression of cytokeratin and vimentin intermediate filaments (IFs), form the immature nucleus pulposus (NP) of the intervertebral disc. As humans age, NCs give way to mature NP cells, which do not possess a vacuolated morphology and typically only express vimentin IFs. In light of their concomitant loss, we investigated the relationship between cytosolic vacuoles and cytokeratin IFs, specifically those containing cytokeratin-8 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…This result indicated that somite-derived sclerotomal cells differentiation is major in untransfected control. Although KRT18 and CDH2 were strongly induced, cytosolic vacuolar structures typically found in human mature juvenile NC were not observed [55][56][57][58]. In addition, the low expression of CA12 and LGALS3 at day 7 indicated that differentiated NLC maintains an immature/embryonic state.…”
Section: Noto Mrna Transfection and Wnt Signalling Activity Are Suffimentioning
confidence: 91%
“…This result indicated that somite-derived sclerotomal cells differentiation is major in untransfected control. Although KRT18 and CDH2 were strongly induced, cytosolic vacuolar structures typically found in human mature juvenile NC were not observed [55][56][57][58]. In addition, the low expression of CA12 and LGALS3 at day 7 indicated that differentiated NLC maintains an immature/embryonic state.…”
Section: Noto Mrna Transfection and Wnt Signalling Activity Are Suffimentioning
confidence: 91%
“…CK14, a cytoskeletal protein that is found in all types of epithelial cells of all different types, was also studied. [ 56 ] As a result, the dark brown color in Figure 9 A underlines the epidermis, while the dermis, comprised of collagen, is completely devoid of CK14. CK14 expression in the BC–PVA@SSga group on day 14 highlighted the complete re‐epithelization, while in the other groups, they did not achieve high expression until day 14 due to the lower wound healing ability of BC–PVA@SSg and Nacl 0.9%.…”
Section: Resultsmentioning
confidence: 99%
“…hMSCs were seeded onto surfaces and grown overnight. Cytochalasin‐D‐treated hMSCs had their media replaced with growth media containing 10 μmol/L cytochalasin‐D for 1 h prior to fixing . Samples were chemically fixed using 4% formaldehyde and 1% sucrose solution and permeabilized with a 300 mmol/L sucrose, 50 mmol/L sodium chloride, 6 mmol/L magnesium chloride, 20 mmol/L HEPES, and 0.5% Triton‐X‐100 solution.…”
Section: Methodsmentioning
confidence: 99%